PREVALENCE OF DIABETES MELLITUS WITH PULMONARY TUBERCULOSIS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA 2016 - Heronimus Hansen Kaware; Deby Kusumaningrum; Arief Bakhtiar (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlight: 1. The signs and symptoms of patients with pulmonary tuberculosis and those of diabetes mellitus were similar.2. Male, aged 51-75 years old, and working in private sector are characteristics of most of the diabetic patients with pulmonary tuberculosis. Abstract: Background: Diabetes Mellitus is a type of disorder where the patients' blood sugar is above average. Diabetes Mellitus can cause an abundance of comorbidities, from viral infection until metabolic abnormalities. The increased risk of infections is mostly because diabetes mellitus changes how the body works. The changes range from changes in mechanical barriers (humoral immunity) and cellular changes (cellular immunity), the changes of the humoral immunity that can increase the chance of protracting pulmonary tuberculosis. Objective: The purpose of this study was to describe the characteristics of diabetes mellitus in pulmonary tuberculosis in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia from January to December 2016. Materials and Methods: The research method used was an observational study using a cross-sectional design conducted in Central Medical Record for hospitalized patients, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The diabetes mellitus patients' data collected from the medical records of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2016 were 1,410 and 11 of them were also diagnosed with pulmonary tuberculosis. The final data taken were from 67 out of 115 patients due to the incomplete medical record. Results: According to the data, the most of the diabetic patients with pulmonary tuberculosis were male, age of 51-75 years old, and worked in private sector. Conclusion: There was a significantly higher number of diabetes mellitus withpulmonary tuberculosis patients in older age, males,and private-sector workers. Diabetic patients with pulmonary tuberculosis weremostlymale,aged 51-75 years old, andworked in private sector.